Discovery of a novel dual functional phenylpyrazole-styryl hybrid that induces apoptotic and autophagic cell death in bladder cancer cells - Leong, Sze Wei; Wang, JingJing; Okuda, Kazuhide Shaun; Su, Qi; Zhang, Yanmin; Abas, Faridah; Chia, Suet Lin; Yusoff, Khatijah (Elsevier, 2023)
Unpleasant side effects and resistance development remained the Achilles heel of chemotherapy. Since low tumor-selectivity and monotonous effect of chemotherapy are closely related to such bottleneck, targeting tumor-selective multi-functional anticancer agents may be an ideal strategy in the search of new safer drugs. Herein, we report the discovery of compound 21, a nitro-substituted 1,5-diphenyl-3-styryl-1H-pyrazole that possesses dual functional characteristics. The 2D- and 3D-culture-based studies revealed that 21 not only could induce ROS-independent apoptotic and EGFR/AKT/mTOR-mediated autophagic cell deaths in EJ28 cells simultaneously but also has the ability in inducing cell death at both proliferating and quiescent zones of EJ28 spheroids. The molecular modelling analysis showed that 21 possesses EGFR targeting capability as it forms stable interactions in the EGFR active site. Together with its good safety profile in the zebrafish-based model, the present study showed that 21 is promising and may lead to the discovery of tumor-selective multi-functional anti-cancer agents.